2017
DOI: 10.1088/1748-9326/aa5f3f
|View full text |Cite
|
Sign up to set email alerts
|

Hydropower versus irrigation—an analysis of global patterns

Abstract: Numerous reservoirs around the world provide multiple flow regulation functions; key among these are hydroelectricity production and water releases for irrigation. These functions contribute to energy and food security at national, regional and global levels. While reservoir operations for hydroelectricity production might support irrigation, there are also well-known cases where hydroelectricity production reduces water availability for irrigated food production. This study assesses these relationships at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 29 publications
(25 reference statements)
2
55
0
Order By: Relevance
“…(vi) The relationship between hydropower and irrigation in multipurpose reservoirs is pivotal: it has been evaluated that while today roughly 54% of global installed hydropower capacity competes with irrigation and 8% complements it, competition is expected to intensify under a warmer climate (Zeng et al, 2017).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…(vi) The relationship between hydropower and irrigation in multipurpose reservoirs is pivotal: it has been evaluated that while today roughly 54% of global installed hydropower capacity competes with irrigation and 8% complements it, competition is expected to intensify under a warmer climate (Zeng et al, 2017).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In the last decades (in particular during the wet season in unimodal rainfall climates, where rain falls only during one period per year) prolonged droughts have resulted in severe power crises in several hydropower-dependent countries (including for instance, in Kenya, Tanzania, Ghana, Zimbabwe and Zambia during the 2015-16 El Niño period, characterized by oceanic and atmospheric shifts in the Pacific Ocean which affect weather and climate across the tropics, and in Malawi in 2017), with frequent outages, power rationing , adverse business experience (Gannon et al, 2018) to emergency (and costlier) IPP (independent power producer)-provided dieselfired generators . Water availability issues represent a growing source of risk in different areas, also due to an increasing competition between water use for power generation, irrigation, and municipal water supply (Zeng et al, 2017;.…”
mentioning
confidence: 99%
“…Water stored in dams can be used for irrigated agriculture [19] as well as hydropower generation. Irrigated agriculture land will foster greater food security and electricity generated from hydropower will contribute to large scale grid-based electrification which will in turn boost industrial outputs, economic growth and human development [20].…”
Section: Introductionmentioning
confidence: 99%
“…The recent publication by Zeng et al (2017) highlights the trade-offs inherent in managing water resources for multiple demands, focusing specifically on hydropower generation versus deliveries for agricultural irrigation supply. At the global scale, the authors found that over half of all installed hydropower competes with irrigation, broadly.…”
mentioning
confidence: 99%
“…As the analysis by Zeng et al (2017) makes clear, global water security will be dependent upon several interacting forces that govern water managed for hydropower, irrigation, and ecosystems. Wada and Bierkens (2014) and others have also made it clear that the future sustainability of human water use is doubtful.…”
mentioning
confidence: 99%